Estrategias social media para el fortalecimiento comercial de la microempresa Adangels de la ciudad de Guayaquil - Fuentes Vera, Lissette Viviana (2017)
The present project proposes the development of social media strategies for the commercial strengthening of the Adangels microenterprise located in the city of Guayaquil, which allows the organization to take advantage of the online tools to improve the quality of the service, as well as have a fluid and direct communication with clients so that the company can take advantage of this feedback to better understand their needs and improve services, offering consumers an added value. The methodological design chosen was a bibliographic research of a descriptive type, supported by the inductive-deductive method, based on the formulation of the problem, how the use of social media strategies will commercially strengthen Adangels microenterprise of the city From Guayaquil?............